2003
DOI: 10.1073/pnas.2033934100
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 interacts with RAR1 and SGT1 and is essential for RPS2-mediated disease resistance in Arabidopsis

Abstract: RAR1 and its interacting partner SGT1 play a central role in plant disease resistance triggered by a number of resistance (R) proteins. We identified cytosolic heat shock protein 90 (HSP90), a molecular chaperone, as another RAR1 interacting protein by yeast twohybrid screening. RAR1 interacts with the N-terminal half of HSP90 that contains the ATPase domain. HSP90 also specifically interacts with SGT1 that contains a tetratricopeptide repeat motif and a domain with similarity to the cochaperone p23. In Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
423
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(446 citation statements)
references
References 43 publications
14
423
1
1
Order By: Relevance
“…Pharmacological and genetic evidence supports the view that HSP90s also play a critical part in disease resistance mediated by another Arabidopsis NB-LRR protein, RPS2, upon recognition of its corresponding P. syringae effector, AvrRpt2 [8]. Either treatment with the HSP90 inhibitor geldanamycin or null mutation of AtHSP90.1 impaired an efficient resistance response to P. syringae expressing avrRpt2 and had weak effects on RPM1-dependent immunity.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Pharmacological and genetic evidence supports the view that HSP90s also play a critical part in disease resistance mediated by another Arabidopsis NB-LRR protein, RPS2, upon recognition of its corresponding P. syringae effector, AvrRpt2 [8]. Either treatment with the HSP90 inhibitor geldanamycin or null mutation of AtHSP90.1 impaired an efficient resistance response to P. syringae expressing avrRpt2 and had weak effects on RPM1-dependent immunity.…”
mentioning
confidence: 74%
“…So far, genetic approaches have identified relatively few components required for R gene function in plants [5]. A highly conserved protein class, the heat-shock proteins, has now been added to the list and work on these proteins promises to provide fresh insights to the molecular mechanics of the pathogen recognition process [6][7][8][9].…”
mentioning
confidence: 99%
“…However, several pieces of evidence might provide some clues to this question. Takahashi et al (2003) and HvHSP90 co-immuno-precipitated with HvSGT1 in barley plants [98]. The HSP90 proteins are members of the heat shock protein superfamily that are implicated in protein complex maturation, in the activation of innate immune system, and in regulating the activity of many signal transduction proteins [99][100][101].…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%
“…The function of these proteins in disease resistance responses have been extensively investigated previously using mutant analyses Chandra-Shekara et al, 2004;Hubert el al., 2003;Lu et al, 2003;Shirasu et al, 1999;Takahashi et al, 2003) and by virus induced gene silencing (VIGS) analyses in several plant species (Bhattarai et al, 2007;de la Fuente van Bentem et al, 2005;Leister et al, 2005;Liu et al, 2004;Scofield et al, 2005). The data from these studies revealed differing specificities for these proteins in diverse NB-LRR-mediated resistance responses.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown in Arabidopsis that RAR1 and HSP90, but not SGT1, are required for RPM1-, RPS2-, and RPS4-mediated immune responses Hubert et al, 2003;Takahashi et al, 2003). Similarly, RPP2-mediated resistance requires SGT1 but not RAR1.…”
Section: Discussionmentioning
confidence: 99%